The Myth of Efficiency - Rothbard, Murray N. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
The author criticizes the concept of efficiency and emphasizes that it is much less sustainable when economists employ it for the aggregate of the society. The systemic failure of economic thinking to describe world’s reality is the result of the utilitarian philosophy that has dominated the economy for a century and a half. Utilitarianism suggests that the purpose of all individuals are actually the same , which leads the utilitarians to see all social conflict as technical and pragmatic, and that they can be solved provided that suitable means for common purposes were discovered and adopted. He calls this “myth of the ordinary and universal order”, which makes economists believe they can “scientifically” and somehow free of values prescribe what public policies should be adopted. For Rothbard, however, economists have to get used to the idea that not all life can be encompassed by economic theory. A painful lesson, no doubt, but that is offset by the realization that it may be good for our souls realize their own limits.